PENERAPAN METODE AL MIFTAH LIL ULUM DALAM MENINGKATKAN LITERASI FIQIH (HALAQOTUR ROBIAH) PADA SISWA KELAS VII DI MTs MUALLIMIN MUALLIMAT SUNAN DRAJAT LAMONGAN - Mahmuddah, Lailatul; Achoita, Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by students' low fiqh literacy, due to their weak mastery of the tools and the use of less innovative learning methods. This study aims to describe the application of the Al Miftah Lil Ulum Method and analyze the improvement in fiqh literacy of seventh-grade students at MTs Muallimin Muallimat Sunan Drajat Lamongan. This study used a mixed methods approach with the Kemmis and McTaggart Classroom Action Research (CAR) model, implemented in two cycles. Data collection techniques included observation, testing, and documentation. Data analysis was conducted using qualitative and quantitative methods. The results showed that the application of the Al Miftah Lil Ulum Method significantly improved students' fiqh literacy. This was demonstrated by an increase in students' average score from 64.5 in the pre-cycle with 30% completion, to 74.5 in the first cycle with 65% completion, and to 85.5 in the second cycle with 80% completion. Furthermore, student activity and engagement in learning also increased. Thus, the Al Miftah Lil Ulum Method is effective in improving students' fiqh literacy and can be a solution in fiqh learning in Islamic boarding school context.